2008
DOI: 10.1021/la702141h
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of PEO/PS Block Copolymers at the Air/Water Interface:  A Simple Model for Predicting the Size and Aggregation Number of Circular Surface Micelles

Abstract: Isotherms of monolayers of poly(ethylene oxide) (PEO) and polystyrene (PS) triblock copolymers spread at the air/water interface were obtained by film balance technique. In a low concentration regime, the PEO segments surrounding the PS cores behave the same way as in monolayers of PEO homopolymers. Langmuir-Blodgett (LB) films prepared by transferring the monolayers onto mica at various surface pressures were analyzed by atomic force microscopy (AFM). The results reveal that these block copolymers form micell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 45 publications
4
39
0
Order By: Relevance
“…In the so‐called gaseous regime, the low surface density corresponds to a large area per molecule, and the film exhibits a low surface pressure. This small but finite surface pressure indicates that the copolymer remains at the interface, consistent with the known surface activity of PEO homopolymers 2124. With increasing density at the surface due to molecular crowding, a pseudoplateau appears at an area of approximately 15 nm 2 molecule −1 , caused by insertion of PEO segments into the aqueous subphase.…”
Section: Resultssupporting
confidence: 73%
“…In the so‐called gaseous regime, the low surface density corresponds to a large area per molecule, and the film exhibits a low surface pressure. This small but finite surface pressure indicates that the copolymer remains at the interface, consistent with the known surface activity of PEO homopolymers 2124. With increasing density at the surface due to molecular crowding, a pseudoplateau appears at an area of approximately 15 nm 2 molecule −1 , caused by insertion of PEO segments into the aqueous subphase.…”
Section: Resultssupporting
confidence: 73%
“…In previous work, it was found that a fourth polymer with a PEO weight fraction of 0.96 would not form a micelle over the entire pH range from 8 to 2 with or without ionic salts present [2]. A decrease in aggregation number with PEO content has been observed by others [44][45][46] although the variation of aggregation numbers with composition are somewhat more complex than observed for the small number of samples investigated here. This suppression of micellization was attributed to the solubility of the PEO combined with the high fraction of PEO in the polymer.…”
Section: Light Scatteringsupporting
confidence: 44%
“…Thus, volume exclusion by the PEO side‐chains cannot be responsible for bare spots that ranged in size from several nm to ~50 nm (accounting for tip radius effects). The patterns may be due to the adsorption of triblocks from lamellar, worm‐like, or circular micellar conformations caused by the relatively large hydrophobic PBD centerblock and short PEO chains . Phase separation may also occur during self‐assembly; indeed, the surface features are morphologically similar to those observed in spin‐cast thin films of diblock copolymers .…”
Section: Resultsmentioning
confidence: 87%